Financial Regulation as a Control System Problem: The Case of the Savings & Loan Industry - Balderston, F. E. (Management Science, 1966)
Operations and regulation of the savings and loan industry are evaluated in terms of four subsystems: (1) market structure, in which the market environment and the policies of the individual firm are important determinants, but in which, the regulatory authorities have licensing power with respect to the number of firms and branch offices; (2) transactions, which divides into transactions in the capital inflow, or savings, market, and in the capital placement, or lending, market; (3) liquidity, in which the firm's cash flows and liquidity requirements are augmented by the Federal Home Loan Bank system; and (4) safety, in which, the strength of the housing market, the portfolio and reserve position of tie individual institution, and insurance of accounts by the FSLIC are determining factors. The paper discusses the interplay between environment, executive decision and regulatory influence in each of these subsystems and also points to interactions between the subsystems.